Influence of physician and clinical dietitian on the use of dietary supplements among Polish patients with ulcerative colitis – pilot study - MACKOW, Monika; NOWACKI, Dorian; GAJDA, Robert; STAWARSKI, Andrezj; NEUBAUER, Katarzyna (Nutrición Clínica y Dietética Hospitalaria, 2024)
Introduction: Patients with ulcerative colitis are a group of patients who are particularly vulnerable to nutritional deficiencies. Supplementation, prescribed by a physician or clinical dietitian, is therefore important in these patients. Materials and methods: The study was carried out by means of a questionnaire on a group of 106 people diagnosed with colitis and in remission. Results: More than 92% recommended the use of dietary supplements. Vitamin supplements were most common among people with ulcerative colitis (82.7%). The physician as a source of knowledge positively influenced the use of vitamin and mineral supplements (r=0.23, p=0.0213) while dietitians as a source of knowledge showed no significant effect on patients’ supplementation choices. Conclusion: In Poland, the physician is the main source of supplementation knowledge than the clinical dietitian. This may be due to the unregulated nature of the dietitian profession in the Polish health care system. . It is therefore necessary to integrate dietitians in Poland into the medical profession, which will allow for better results in the treatment of not only IBD patients.